Perspectives on Islamic Banks Activity in light of Money Creation and Cash Reserve Ratio (CRR) - Benlala, Mejd Aures (مجلة الباحث للدراسات الأكاديمية, 2023)
Islamic economics principles state that Islamic banks are economic institutions that must comply with the rules of Islamic economic legislation, whether in terms of financing, or in terms of monetary policy. The Sharia stipulates that money does not generate money, and that profit and money increase are linked to production, or trade through Murabaha, or Mudharaba and Musharakah, and the like. Given that the Islamic economy depends on what may be called the real economy that is based on production, these principles do not agree with the policy of central banks and their financial/monetary policy, whether in terms of the policy of the cash reserve ratio (CRR), which must be available (deposited) in the central bank, or in terms of the bank’s creation of money without a reciprocal or productive process. This paper aims to identify and address these issues according to an economic, legal and Islamic analysis